2019
DOI: 10.4028/www.scientific.net/msf.944.488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Final Annealing Temperature on Corrosion Resistance of SZA-6 Zirconium Alloy Cladding Tubes

Abstract: The corrosion resistance of SZA-6 zirconium alloy(Zr-0.5Sn-0.5Nb-0.3Fe-0.015Si) cladding tubes finally annealed at 480°C, 510°C and 560°C were studied by static autoclave in 360°C/18.6 MPa pure water and 360°C/18.6 MPa/0.01 mol/L LiOH aqueous solution. The microstructure of the samples before and after corrosion were analyzed by EBSD, TEM and SEM. The results showed that the corrosion weight gains of the three SZA-6 alloy samples were lower than that of Zr-4 alloy after 500 days corrosion in both hydrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…N36 alloy has the largest weight gain, N3 alloy in the intermediate and N2 alloy the smallest. Whereas, the corrosion resistance of Zr-4 obviously changes from the worst in 360 °C pure water [ 5 , 26 ], the intermediate at 390 °C/10.3 MPa and 416 °C/10.3 MPa, to the best at 455 °C/10.3 MPa in superheated steam, which suggests that the temperature-sensitivity of uniform corrosion are quite different between Zr–Sn–Nb alloys and Zr–Sn alloy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N36 alloy has the largest weight gain, N3 alloy in the intermediate and N2 alloy the smallest. Whereas, the corrosion resistance of Zr-4 obviously changes from the worst in 360 °C pure water [ 5 , 26 ], the intermediate at 390 °C/10.3 MPa and 416 °C/10.3 MPa, to the best at 455 °C/10.3 MPa in superheated steam, which suggests that the temperature-sensitivity of uniform corrosion are quite different between Zr–Sn–Nb alloys and Zr–Sn alloy.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is found that Zr-4 alloy is very particular with its temperature-sensitivity behavior because of the intersection in fitting curves of both pre-exponential constant and transition time. Although it is the worst corrosion-resistant alloy in service temperature lower than 360 °C [ 5 , 26 ], as temperature raising, its pre-exponential constant becomes the smallest and the transition time becomes the longest among all the four materials above 427 °C.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 2, the magnetron deposition of the Cr coating on the outer surface of the RUW E110 alloy did not affect its hardness using the applied deposition parameters. The maximal temperature of the RUW alloy during Cr coating deposition (390 °C) was less than the typical annealing temperature of Zr alloy cladding tubes and welds (500-580 °C) [34,35]. The hydrogenation of RUW specimens led to the hardening of both types of specimens (Cr-coated and uncoated) due to a formation of the δ-ZrH phase.…”
Section: Hardness Measurementsmentioning
confidence: 93%
“…Nevertheless, the thermal treatment temperature of the Cr coated Zr alloy should be strictly controlled based on the following three considerations: firstly, the final annealing temperature of the commercially used Zr alloy cladding tubes is about 500 °C [102]. A higher pretreatment temperature of the Cr coated Zr alloy leads the phase transition of the Zr substrate (850 °C), which may affect the mechanical properties and corrosion resistance of the Zr substrate [103]. Secondly, the inter-diffusion between the Cr coating and the Zr substrate would be facilitated by the high temperature, which is one of the main consumption ways of Cr coatings [104].…”
Section: Pretreatmentmentioning
confidence: 99%